Analisis Kinerja Laporan Keuangan Perusahaan Berdasarkan Economic Value Added (EVA) - Budi Zulfachri; M. Syafnur; Nurfitri Zulaika; M. Isa Alamsyahbana; Salihi Salihi (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Covid-19 has an impact on various fields, especially the economic sector, where offices and some industries are prohibited from operating so that companies will lack capital due to declining sales and investors are hesitant to invest. So the company must be optimal in managing finances so that the company can continue to operate. In addition, companies must also pay attention to financial performance reports to attract investors to invest their capital. The purpose of this study was to examine the financial performance of PT Erajaya Swasembada Tbk using the Economic Value Added (EVA) method during the period 2016 – 2020. The data collection technique used in this study was the documentation method by looking at the financial statements and general description of PT Erajaya Swasembada Tbk. The results obtained from the analysis of financial performance based on the Economic Value Added at PT Erajaya Swasembada Tbk for the 2016-2020 period show a positive EVA, meaning that management has succeeded in creating economic value Added for the company so that the company can fulfil its obligations to investors and other funders.